INVENTARISATION OF CORAL REEF FISHES IN THE NATIONAL CONSERVATION AREA, ANAMBAS ISLANDS, PROVINCE OF RIAU ISLANDS - Joni '; Syafruddin Nasution; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research on coral fish species conducted in some islands in the Anambas waters. This research aims to identify the species of coral fish present in the Anambas waters. This research has been conducted from April to May 2016. The research station, includes five islands, namely the Langok, Kelong, Mengkian, Siantan Lembong and Siantan Teluk Gambut island. Samples were collected by using line fishing and gill net. The results showed that there were 3 orders, 16 families and 30 genera includes 59 species of coral fish. The most common fishes present were the member of Scaridae, Labridae and Nemipteridae, namely C. Bowersi, S. ghobban, S. quoyi, C. Anchorago , H. Melapterus and P. trivittatus.Key word: Coral fish, Anambas islands, Province of Riau Islands